EFFECT OF HEUTAGOGY FACILITATED BY MOBILE TECHNOLOGY IN TEACHING AND LEARNING OF AUTOMOBILE MECHANICS IN HIGHER EDUCATION OF SOUTH EASTERN NIGERIA - Areji, Jonathan Nwagboliwea (Journal of Continuing and Development Education, 2023)
The study focuses on the facilitation of Heutagogy by Mobile technology. Specifically, this study was amid at finding the effect of heutagogy facilitated by mobile technology on Polytechnic students’ achievement in automobile mechanic. The population of the study was 154 final year students - 80 students were selected using a simple random technique as the study sample size. MCATAMS questionnaire for data collection was employed, Data were analyzed using t-test and it was observed that there was no significant difference between mean achievements of the groups at 0.05 level of significance. The effect size of post – test was determined using Cohens’d. The result of the finding showed that only the experimental group pre – test scores departed significantly from the normal distribution (W(40) =-889, P =-001), indicating a moderate increase on the experimental students’ achievement test. It was found that adopting heutagogy as a teaching and learning method moderately increased students’ achievement in automobile mechanics. It is recommended that the present study be replicated among adult and young learners to increase confidence in the study.